How Can We Enhance PISA Ranking Through Effective Learning Methods? Systematic Literature Review From 2019 to 2024 - Abi Fa'izzarahman Prabawa; Henny Indreswari; Arbin Janu Setiyowati; Salwa Mahalle (Jurnal Pendidikan Progresif, 2024)
Objective: The research aims [P1] to identify effective learning methods to improve Programme for International Student Assessment (PISA) rankings; this study undertakes a comprehensive analysis of relevant literature. PISA results provide a benchmark for assessing students' reading, mathematics, and science literacy abilities—crucial indicators of a nation's educational success. Most countries within the OECD utilize PISA assessment results to shape their educational policies. As nations strive to enhance their educational frameworks, particularly in teaching methodologies, the pursuit of influencing PISA rankings becomes increasingly competitive. Countries with lower PISA rankings often look to adopt best practices in literacy improvement from those with higher rankings. This study aspires to deliver best practices to bolster students' literacy skills, thereby improving PISA standings. Methods: The systematic literature review (SLR) is designed by the PRISMA diagram flow, encompassing the critical stages of identification, screening, eligibility, and inclusion. The SLR draws from 14 articles sourced from the Scopus database. Findings: The findings reveal that innovative teaching approaches, such as context-based learning and the integration of digital tools, significantly enhance students' performance in reading, mathematics, and science literacy. Notably, reading literacy is improved through the Cooperative Integrated Reading and Composition (CIRC) model, which focuses on collaborative learning. Mathematics literacy benefits from STEM-themed materials that bridge abstract concepts to real-world applications and through oral questioning techniques that foster critical thinking. Science literacy skills are advanced through digital comic materials, simplifying complex concepts, while STEM learning applications enhance students' understanding and engagement. Conclusion: In conclusion, this study underscores the vital role of appropriate teaching methods in improving learning outcomes and boosting student engagement in the international PISA assessment. By strategically adopting effective educational strategies from countries with higher PISA rankings, significant advancements can be made, offering hope for the future of education. Keywords: learning, method, PISA.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.2024100